EVALUATION OF ACCOUNTING INFORMATION SYSTEMS ON BUDGETING, USE AND REPORTING OF FUNDS REGULAR SCHOOL OPERATIONAL AID (BOS). (CASE STUDY IN SMA NEGERI 4 KOTA SERANG BUDGET YEAR 2020) - Deny Aditya; Khoirunnisa, Dini; Fahmi Ramadhan, Muhammad (Review of Accounting and Taxation, 2023)
Purpose - This study aims to analyze and determine the application of Accounting Information Systems in the field of Budgeting, Use and Reporting of Regular School Operational Assistance (BOS) Funds at SMA Negeri 4 Kota Serang. Design/methodology/approach - The research was conducted at SMA Negeri 4 Kota Serang. This study uses a qualitative approach. Qualitative Approach Method is a research method based on the philosophy of post positivism used to examine the condition of natural objects, where the researcher is the key instrument. Finding - The Accounting Information System related to the BOS Fund has actually existed since 2019 and was socialized in early 2020. This application created by the Ministry of Education and Culture has been able to accommodate all financial activities from the Regular School Operational Assistance Fund but in its implementation there are many components of incomplete item names, making it difficult for users to operate. A good system is a system that is made to make it easier for users to operate, understandable and structured. Originality - The budget will be able to run effectively based on the time of planning before budgeting, good and careful planning will ensure that the budget implementation function can run effectively and efficiently as expected